Tutor Perceptions of Division I College Athletes - Molly Harry; Amanda Hoffman (University of Kansas Libraries, 2023)
Research regarding athletics stakeholders' (e.g., faculty, non-athlete peers) perceptions of Division I college athletes is abundant and demonstrates that most stakeholders hold negative and stereotypical views of athletes. However, despite their time spent with athletes, little is known about the perceptions academic tutors have toward the athletes they are brought in to assist. Thus, through the lens of stereotype threat, this study explored graduate(d) and undergraduate tutors' (n = 67) perceptions of athletes from three academically and athletically elite Division I institutions. Tutors' perceptions were examined and compared based on their responses to an adapted situational attitude scale survey using correlations, t-tests, and Fisher's Z tests. In general, results suggested tutors did not maintain stereotypical perceptions of the athletes they worked with, a key difference from previous scholarship in this area. Still, graduate(d) tutors generally held athletes to higher academic standards compared to undergraduate tutors. Implications for sport practitioners in academic support programs for athletes include hiring more graduate(d) tutors to work with athletes and fostering stronger relationships between tutors and athletes. Ultimately, this study expands upon the previous research on perceptions and stereotypes of athletes and the findings may demonstrate a shift toward more positive and strengths-based perceptions of Division I athletes.